Horizon Problem and Firm Innovation: The Influence of CEO Career Horizon, Exploitation and Exploration on Breakthrough Innovations - Cho,Sam Yul; Kim,Sang Kyun (Research Policy, 2017)
Building on labor market evaluations and legacy conservation motivation perspectives, we propose a mechanism to explain the relationship between CEO career horizons and breakthrough innovations. Using 10-year panel data from 681 U.S. firms, we find that firms that have a CEO with a short career horizon (measured by CEO age) tend to produce fewer breakthrough innovations. We also find that the relationship between CEO career horizon and breakthrough innovation is partially mediated by R&D spending, and also moderated by organizational learning behavior (exploration vs. exploitation). This study highlights how a CEO’s motivation to protect success in the short term affects the firm’s innovativeness.
Keywords: Strategy & Entrepreneurship